Distribution And Density Of Mangrove Snail (Telescopium Telescopium)In Mangroves Ecosystem From Mengkapan Village, Sungai Apit Subdistrict, Siak District, Riau Province - Andriani, Novia; Adriman, Adriman; Sumiarsih, Eni (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Telescopiumtelescopiumhas significant ecological and economical rolein the mangrove ecosystem. However, information on the distribution and density ofthis snailis rare. To understand the distribution pattern of this snail in the  mangrove ecosystem of Mengkapan Village, a study has been conducted on February 2018. There were 3 transect lines, in the natural area (S1), in the ecotourism area and human inhabitant area (S2) and in the human activity area (S3). In each line, there were 6 plots (1mx1m). The snails were collected manually once/ 2 weeks, 3 times. Distribution pattern and density of the snail were studied.  Results shown that in the S1 and S3 the snail distributed evenly, while that of the S2 was grouped. Distribution Index value of the snail was 0.09-1.09. The highest density was in the S2 (5.17 organisms/ m2)  and the lowest was in the S1 (4.33 organisms/m2). Keywords: Mangrove organisms, distribution patterns, distribution index,Mengkapanvillage, mangrove snail